ANALISIS PENGGUNAAN ACCESS CONTROL LIST (ACL) DALAM JARINGAN KOMPUTER DI KAWASAN BATAMINDO INDUSTRIAL PARK BATAM - Simanjuntak, Pastima; Suharyanto, Cosmas Eko (Journal Information System Development (ISD), 2017)
Routers provide the ability to filter traffic, such as blocking Internet traffic, with access Control Lists (ACLs). ACL is a list of a series of licensing or rejection statement applied to the network address or protocol layer on top. The purpose of this study is to determine the effect of the access control list in the area of network computer in Batamindo Industrial Park Batam. The method used in this research is descriptive and verification methods. The samples are 101 IT employees in Batamindo Industrial Park Batam. And in the formulation of the problem obtained from this research is to determine how the benefits of the use of access control lists. The results obtained are perceived first access control list useful, both instrumental Well Network computer, So with this research writer and IT Employees in the Company may determine that the use of access control lists is very important for computer networks in the area Batamindo Industrial Park Batam.